FREQUENCY AND CHARACTERISTICS OF POTENTIAL DRUG-DRUG INTERACTIONS IDENTIFIED IN PATIENTS HOSPITALIZED AT THE INFECTIOUS DISEASES HOSPITAL OF TIRANA - Hudhra, Klejda; Xhafaj, Delina; Jucja, Besnik (European Scientific Journal, ESJ, 2014)
Potential drug-drug interactions (pDDIs) are a serious and frequenthealth issue, leading to often preventable and predictable adverse drugreactions and other negative outcomes. The objective of this study was toassess the frequency of potential drug-drug interactions and characterizethem in patients hospitalized in an Infectious Diseases hospital in Albania.We conducted a cross sectional study in patients discharged from thishospital in Tirana during the period from October 1, 2011 to December 30,2011 and their medical files were consulted. The detection of pDDIs amongprescribed drugs was performed through the Thompson Micromedex®1.0program, independently by two pharmacists. 31.4% (56) of all patientsincluded in the study experienced at least one pDDI, most of which were ofmoderate severity and well documented. Drugs most frequently involved inpotential DDIs were NSAIDs (24.5%), fluoroquinolones (22.4%), andaminoglycosides (14.3%). Most prevalent specific risks due to pDDIs weredecreased effectiveness or decreased plasma levels of one of the drugs(29.6%), increased response or plasma levels of one of the drugs, with risk ofincreased toxicity (26.5%) and increased risk for tendon rupture (9.1%).According to the results of this study, pDDIs in Albania are frequent andpotentially avoidable. Further divulgation and awareness is needed to preventharmful or clinically important drug-drug interactions. The utilization ofappropriate computer programs, pharmacotherapeutic monitoring of patientsand the pharmacist´s presence in the multidisciplinary team are some of therecommended ways for the improvement of hospitalized patients´ treatment.